Green worlds in early modern Italy : art and the verdant earth - Goodchild, Karen Hope; Oettinger, April; Prosperetti, Leopoldine van Hogendorp, 1948- (Visual and material culture, 1300-1700., 2019)
The green mantle of the earth! This metaphor conceives of the vegetation of the earth as a green cloth that drapes the barren earth. Long popular in patristic literature Il mantello verde della terra is a poetical image that ponders the providential greening of the earth on the third day of the Creation. Borrowing from the vocabulary of weaving it epitomizes the Renaissance interest in "fashioning green worlds" in art and poetry. Rachel Carson invoked the phrase to draw attention to environmental damage done to earth's "brilliant robe." Here it serves as a motto for a cultural poetics that made "living nature" an object of renewed interest. The essays gathered in this volume explore the expanding technologies and cultural dimensions of verzure and verdancy in the Italian Renaissance, and the role of painting in shaping the poetics and expression of greenery in the visual arts of the 16th-century and after